2019
DOI: 10.1200/jgo.18.00264
|View full text |Cite
|
Sign up to set email alerts
|

How Providing Cervical Cancer Screening Results via Cell Phone Affects Patient Follow-Up Rates in Western Kenya

Abstract: Purpose Human papillomavirus (HPV) testing is being more widely used in simplified cervical cancer screening protocols in low-resource settings. One challenge to successful implementation is the multiple visits necessary to provide results and follow-up. mHealth strategies may reduce visit burden by providing information through text message. Methods As part of a cluster-randomized trial to compare HPV testing in clinics and community health campaigns in western Kenya, we carried out a mixed-methods study to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
(8 reference statements)
0
17
0
Order By: Relevance
“…Improve the reporting of digital health strategies in the literature: in our review, only 5 studies [ 35 - 37 , 39 , 54 , 57 , 59 ] met the mERA checklist item on replicability, indicating that many of the digital health strategies identified in this review would be difficult to replicate and re-evaluate based on published information. The use of reporting checklists ensures that all relevant information is presented to readers to assist with study reproducibility.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Improve the reporting of digital health strategies in the literature: in our review, only 5 studies [ 35 - 37 , 39 , 54 , 57 , 59 ] met the mERA checklist item on replicability, indicating that many of the digital health strategies identified in this review would be difficult to replicate and re-evaluate based on published information. The use of reporting checklists ensures that all relevant information is presented to readers to assist with study reproducibility.…”
Section: Discussionmentioning
confidence: 94%
“…A fifth study by Lima et al [ 41 ] used random allocation but was excluded from the review of the primary objectives because of the lack of a control group. Huchko et al [ 39 ] reported findings of a mixed methods analysis from a cluster RCT; however, the assignment of the digital health strategy was not randomized; thus, it did not meet the criteria for inclusion in the review of primary objectives. All 27 studies were included in the review of the secondary objectives, that is, to describe the digital health strategies used for cervical cancer control in LMICs and the challenges associated with their implementation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this this version posted September 25, 2020. ; https://doi.org/10.1101/2020.09.23.20200162 doi: medRxiv preprint transmission, and prevention of Human Papillomavirus (HPV). [28][29][30] Based on high reported mobile phone ownership within Kenya and past research documenting success with text message-based delivery of screening results in western Kenya, 31,32 the introduction of a mobile application-based intervention to address gaps in education and provider support appears feasible in this context. The aim of this study was to iteratively develop and refine the mSaada mobile application in consultation with key stakeholders prior to small-scale pilot testing in health facilities in western Kenya.…”
mentioning
confidence: 99%